2019
DOI: 10.1515/biol-2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Co-downregulation of GRP78 and GRP94 induces apoptosis and inhibits migration in prostate cancer cells

Abstract: BackgroundBoth glucose-regulated protein 78 kDa (GRP78) and glucose-regulated protein 94 kDa (GRP94) are important molecular chaperones that play critical roles in maintaining tumor survival and progression. This study investigated the effects in prostate cancer cells following the downregulation of GRP78 and GRP94.MethodsRNA interference was used to downregulate GRP78 and GRP94 expression in the prostate cancer cell line, PC-3. The effects on apoptosis and cell migration was examined along with expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The cell surface GRP78 complexes with different proteins involved in cell survival and proliferation such as α 2‐macroglobulin and Cripto [28,29] . Downregulating GRP78 and GRP94 in the PC‐3 prostate cancer cell line resulted in a higher rate of apoptosis through activating caspase‐9 and increasing the Bax/Bcl‐2 ratio [30] . Furthermore, silencing GRP94 in PANC‐1 cells enhanced the actinomycin D induced cell death [27] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell surface GRP78 complexes with different proteins involved in cell survival and proliferation such as α 2‐macroglobulin and Cripto [28,29] . Downregulating GRP78 and GRP94 in the PC‐3 prostate cancer cell line resulted in a higher rate of apoptosis through activating caspase‐9 and increasing the Bax/Bcl‐2 ratio [30] . Furthermore, silencing GRP94 in PANC‐1 cells enhanced the actinomycin D induced cell death [27] .…”
Section: Resultsmentioning
confidence: 99%
“…[28,29] Downregulating GRP78 and GRP94 in the PC-3 prostate cancer cell line resulted in a higher rate of apoptosis through activating caspase-9 and increasing the Bax/Bcl-2 ratio. [30] Furthermore, silencing GRP94 in PANC-1 cells enhanced the actinomycin D induced cell death. [27] Arctigenin, the first discovered antiausterity agent against pancreatic cancer, displayed its preferential cytotoxic activity under nutrient-deprived condition partially through inhibition of the unfolded protein response markers GRP78 and GRP94.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Tolerance to various cytotoxins was provided by GRP78 and GRP94 overexpression in several cell lines [31]. Furthermore, the co-downregulation of GRP78 and GRP94 expressions in prostate cancer cells by their specific siRNAs suppressed cell migration and promoted caspase-9-dependent apoptosis [36]. In the present study, transient transfection of HEI-OC1 cells with siRNA targeted against GRP78 or GRP94 abolished both inducers' expression levels during ER stress preconditioning and failed to reduce cisplatin-mediated ROS accumulation, thus sensitizing cells to cisplatin-induced cytotoxicity ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is involved in many signaling pathways related to the apoptosis and proliferation process (MAPK and AKT/S6 signaling pathways). In the study by Lu et al [110], it has been shown that GRP94 along with another chaperone protein, GRP78, are expressed in the cytoplasm and cell membrane in prostate cancer tissue cells, while in benign prostate hyperplasia tissue the expression is negligible. It has been proven that the simultaneous silencing of GRP78 and GRP94 expression with the use of small interfering RNAs (siRNAs) in PCa cells, increases the apoptosis process, by increasing the expression of the Bax protein and significantly inhibiting the migration of tested cancer cells, as a result of a significant inhibition of vimentin expression [110].…”
Section: Hsp90 and Prostate Cancer And Benign Prostatic Hyperplasiamentioning
confidence: 99%